The phylogenetic analysis of the new emerging ALV-K revealing the co-prevailing of multiple clades in chickens and a proposal for the classification of ALV-K - Guo, Jinhan; Deng, Qiaomu; Zhu, Weiyu; Fu, Fumei; Liu, Linmin; Wei, Tianchao; Wei, Ping (Frontiers in Veterinary Science, 2023)
Subgroup K avian leukosis virus (ALV-K) is a new subgroup of avian leukosis virus (ALV) that was first defined in 2012 and has been become prevalent in Chinese native chickens in recent years. An in-depth analysis of the genetic diversity of ALV-K was performed in the study. By Blast analysis, the env gene and the sequences of the 25 ALV-K isolates we isolated were found to be closely related to the isolates from Guangdong, Hebei, Jiangsu, and Hubei provinces, China. Further eighty-nine sequences of the gp85 gene of ALV-K strains available were used in the phylogenetic and genetic distance analyses for the classification. ALV-K was divided into two second-order clades (Clades 1.1 and 1.2) and three third-order clades (Clades 1.2.1, 1.2.2, and 1.2.3), indicating that not only 1.1 and 1.2.3, the two old clades which are prevalent in Japan, but also two new clades (1.2.1, 1.2.2), are co-prevalent in China. The representative strains of each clade were defined for the first time. Notably, Clade 1.2.2 was found to have a deletion of an amino acid residue in the gp85 gene, which was obviously different from Clades 1.1, 1.2.1, and 1.2.3. The proposed classification method will facilitate future studies of ALV-K epidemiology and the comparison of sequences obtained across the world. The first global comprehensive molecular epidemiological analysis was accomplished on the emerging ALV-K.